Indeks Bisnis UMKM sebagai Indikator Kemajuan UMKM di Indonesia - Dipa Teruna Awaludin; Tedy Ardiansyah (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
Abstract: The purpose of this research is to determine the reason for the differences in the MSME business index for each province in Indonesia, as well as to provide support for the normality of MSME business index data for each province in Indonesia in the fourth quartile of 2021. The research was carried out using a quantitative approach that used the binomial test and the Kolmogorov-Smirnov test. The main data, namely questionnaires, and supporting data, namely books and journals, were used to collect data, where the respondent's data totaled 7,082 MSME debtors, namely MSME actors spread across the provinces where the criteria have been set according to the MSME requirements in the territory of Indonesia, then grouped into 33 provincial data as in the MSME business index table. The analysis test uses the binomial test, and if the binomial probability value, or exact sig value. (2-tailed), of 0.001 is smaller than alpha (0.05), then the null hypothesis can be rejected. Thus, the hypothesis that on average "the average MSME business index = 100 for each province in Indonesia in the 4th quartile of 2021," is declared not accepted, and the Kolmogorov Smirnov test, Sig (2-tailed) = 0.200 because of the Asymp value. Sig (2-tailed) of 0.200 is greater than alpha (0.05), so the null hypothesis cannot be rejected, so it answers the problem formulation and the hypothesis that for the normality of the MSME business index data for each province in Indonesia in the 4th quartile of 2021, the data is normally distributed. Although the average business index has differences, these only occur in 7 provinces, compared to an average above 100 totaling 26 provinces.